Social Capital on the Sustainability of Micro Small and Medium Enterprises for College Students - Yulina Ismiyanti; Sucihatiningsih Dian Wisika Prajanti; Cahyo Budi Utomo; Eko Handoyo (Universitas Negeri Semarang, 2022)
Abstrak. When many industries are stagnant, many people are laid off, and graduate students are unable to find employment, Micro, Small, and Medium Enterprises (MSMEs) are items that need to be taken into consideration. They are seen as economic saviors. The study examines social capital and how it affects Semarang college students' MSMEs sustainability. With a case study methodology, this research is qualitative. Qualitative information was gathered for the study through in-depth interviews, observations, and documentation. Purposive sampling was used to select informants. Eight college students with MSMEs from Semarang's four largest universities UNISSULA, UNNES, UNDIP, and UPGRIS serve as the data's primary sources. Information has been from college students managing MSMEs for at least two years. Through the steps of data reduction, data display, and conclusion and verification, data analysis included interactive analytical methodologies. The findings of this study suggest that MSMEs college students acquire capital through their social connections with other businesspeople, vendors, clients, families, parking attendants, locals, and other students. The approach for maintaining student MSMEs involves managing time between classes and MSMEs, capital, manufacturing, and marketing. The technique used by college students’ MSMEs is to improve and grow their offline and online customer networks, collaborate with other traders in marketing activities, offer enticing bonuses to clients, and utilize school resources to help with financing issues.